Relevansi living value assessment dalam mata pelajaran sejarah kebudayaan Islam di MA Al Falah - Setiady, Dicky; Fauzan, Fauzan; Rusadi, Bobi Erno; Isnaini, Muhammad (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2025)
This study addresses the ongoing moral crisis by examining the implementation of a Love-Based Curriculum in Islamic education as a form of value-based learning. Madrasahs are encouraged to innovate instructional practices to foster students’ spiritual and social development through five core values: love for God and the Prophet, love for knowledge, love for oneself and others, love for the environment, and love for the homeland. Using a descriptive qualitative approach, the study applies the Living Value Assessment (LVA) as both a reflective and pedagogical instrument within Islamic Cultural History (SKI) learning at Madrasah Aliyah Al Falah. LVA complements Value-Based Education (VBE) by assessing the internalization of values, while VBE provides the educational framework that supports value growth. Data were collected from reflective journals of four students in Grades X and XI. The findings show that LVA effectively identifies the five dimensions of love embedded in the Love-Based Curriculum and can be used by teachers to evaluate value integration in SKI learning.